Community Based Education Planning - Nasrudin; Sutaryat Trisnamansyah; Iim Wasliman; Hendi Suhendraya (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
Planning is an important and strategic element and provides direction in the implementation of activities to achieve the desired goals or objectives. The focus of this research is community-based education planning which is detailed in research problems, namely curriculum implementation planning and academic planning. This study uses a qualitative approach with data collection techniques including interviews, observations, and documentation studies. Technique of data validity with source triangulation. The data analysis uses the following procedures: data reduction, data presentation, and drawing conclusions. Research results: The curriculum applied at PKBM Miftahul Huda Majalengka uses a mixed curriculum or modification of the national curriculum combined with the Miftahul Huda Majalengka Taklim Council curriculum. The curriculum implementation planning has been made by the teacher. To support the implementation of the curriculum, an academic plan is made. The special academic planning in PKBM Miftahul Huda Majalengka is the Preparatory Class. Suggestions that can be given: (1) So that every teacher makes a complete curriculum implementation plan. (2) Recruitment of teaching staff according to their specialization.